How Wiles v the University of Auckland strengthens academic freedom in New Zealand - Hendy, Shaun (New Zealand Science Review, 2025)
While academic freedom is embedded in the New Zealand Education and Training Act 2020, the Act is not explicit as to how the resulting rights and corresponding obligations should be exercised by universities and their staff. The recent employment court judgment in favour of Associate Professor Siouxsie Wiles in her dispute with the University of Auckland highlighted how the broader environment in which academic commentators participate has deteriorated, with women or those from minority groups, targeted with threats and abuse when they step into the public sphere. The judgment also demonstrated that even when the principles of academic freedom are embedded in policies and employment contracts, this does not always translate into practice. As Dr Wiles’ case shows, the statutory responsibility of universities in New Zealand to preserve and enhance academic freedom requires a genuine and active commitment from senior management.